2013
DOI: 10.4049/jimmunol.1200615
|View full text |Cite
|
Sign up to set email alerts
|

Divergence in CD19-Mediated Signaling Unfolds Intraclonal Diversity in Chronic Lymphocytic Leukemia, Which Correlates with Disease Progression

Abstract: Emerging data on intraclonal diversity imply that this phenomenon may play a role in the clinical outcome of patients with chronic lymphocytic leukemia (CLL), where subsets of the CLL clone responding more robustly to external stimuli may gain a growth and survival advantage. In this study, we report intraclonal diversity resolved by responses to CD19 engagement in CLL cells, which can be classified into CD19-responsive (CD19-R) and -nonresponive subpopulations. Engagement of CD19 by anti-CD19 Ab rapidly induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 49 publications
(56 reference statements)
2
19
0
Order By: Relevance
“…There is evidence to suggest a role for CD19 in enhancing malignant pathways (10). For example, high levels of CD19 expression were shown to correlate with Akt activation and overexpression of c-Myc (12,13). Targeting CD19 in vitro seems to confer antitumor activity by induction of cell-cycle arrest (14), apoptosis (9), and sensitization of neoplastic cells to chemotherapy (15,16).…”
Section: Cd19 As a Targetmentioning
confidence: 99%
“…There is evidence to suggest a role for CD19 in enhancing malignant pathways (10). For example, high levels of CD19 expression were shown to correlate with Akt activation and overexpression of c-Myc (12,13). Targeting CD19 in vitro seems to confer antitumor activity by induction of cell-cycle arrest (14), apoptosis (9), and sensitization of neoplastic cells to chemotherapy (15,16).…”
Section: Cd19 As a Targetmentioning
confidence: 99%
“…This is also in line with previous studies, which found that sHLA-G levels in plasma were higher in CLL patients than in healthy controls. 17,18 A second issue favoring the view that quantification of soluble rather than membrane HLA-G is an informative and dependable assay derives from old and new facts linked to the unique lipid structure of the CLL cell surface, 33,34 potentially increasing the instability of the membrane form. In agreement with this, in myeloma cells mHLA-G is also released from the cell membrane in microparticles.…”
mentioning
confidence: 99%
“…In a previous study, we found that in some cases aggregation of chronic lymphocytic leukemia (CLL) cells is a physiological outcome of CD19 engagement, and can be measured by flow cytometry . Moreover, we have shown that the extent of CLL cell aggregation in a given patient is associated with disease progression . We show herein that aberrant CLLs exhibit elevated levels of CD19‐induced cellular aggregation, in a similar manner to circulating non‐Hodgkin's lymphoma (NHL) cells.…”
mentioning
confidence: 64%
“…Acquisition of an aggregate as a single event is considered as coincidence, and common flow cytometry protocols recommend the exclusion of such events, pending on their occurrence as random events . In a previous study, we found that in some cases aggregation of chronic lymphocytic leukemia (CLL) cells is a physiological outcome of CD19 engagement, and can be measured by flow cytometry . Moreover, we have shown that the extent of CLL cell aggregation in a given patient is associated with disease progression .…”
mentioning
confidence: 95%
See 1 more Smart Citation